2019
DOI: 10.1002/ange.201913640
|View full text |Cite
|
Sign up to set email alerts
|

f‐Element Half‐Sandwich Complexes: A Tetrasilylcyclobutadienyl–Uranium(IV)–Tris(tetrahydroborate) Anion Pianostool Complex

Abstract: Despite there being numerous examples of f‐element compounds supported by cyclopentadienyl, arene, cycloheptatrienyl, and cyclooctatetraenyl ligands (C5–8), cyclobutadienyl (C4) complexes remain exceedingly rare. Here, we report that reaction of [Li2{C4(SiMe3)4}(THF)2] (1) with [U(BH4)3(THF)2] (2) gives the pianostool complex [U{C4(SiMe3)4}(BH4)3][Li(THF)4] (3), where use of a borohydride and preformed C4‐unit circumvents difficulties in product isolation and closing a C4‐ring at uranium. Complex 3 is an unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The silyl substituents are also prone to undergoing activation by deprotonation. Compounds 1 – 3 therefore expand the very small family of lanthanide and actinide complexes of the pristine Cb′′′′ ligand, [38–41] and represent the first lanthanide metallocene‐like sandwich complexes of such a ligand. Viewed from the perspective of improving SMM properties, the broader significance of complex 1 is that if a method of removing the equatorial borohydride ligand can be devised, the (currently) hypothetical species [(η 4 ‐Cb′′′′)Dy(η 5 ‐C 5 Me 4 t Bu)] could be synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…The silyl substituents are also prone to undergoing activation by deprotonation. Compounds 1 – 3 therefore expand the very small family of lanthanide and actinide complexes of the pristine Cb′′′′ ligand, [38–41] and represent the first lanthanide metallocene‐like sandwich complexes of such a ligand. Viewed from the perspective of improving SMM properties, the broader significance of complex 1 is that if a method of removing the equatorial borohydride ligand can be devised, the (currently) hypothetical species [(η 4 ‐Cb′′′′)Dy(η 5 ‐C 5 Me 4 t Bu)] could be synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…The answer to (1) appears to be predominantly related to the presence of di-or trianionic ligands [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] ; indeed, we have previously found that pseudo-C 3v uranium(V) complexes with terminal nitrido-and oxo ligands tend to behave as belonging to a high-symmetry point group, unlike what their C 1 structures would dictate. 51,57 We found that some of the nitrido-complexes have electron paramagnetic resonance (EPR)-silent m J = G3/2 ground states (silent in true C 3v symmetry), with excited m J = G5/2 states observable by EPR (active even in true C 3v symmetry) lying within a few tens of cm À1 , 51 given the very sensitive nature of EPR, and that we could only observe EPR transitions in the excited state, the ground m J = G3/2 states must be very pure.…”
Section: Electronic Structure Calculationsmentioning
confidence: 98%
“…[19][20][21] Outside of ''simple'' high-symmetry complexes, sufficiently low-symmetry coordination geometries will usually exhibit a singlet (A) spin-orbit ground state 5,7,22 ; this is because uranium(IV) has two unpaired electrons and is thus a non-Kramers ion; hence, there is no requirement for any electronic degeneracies in the J = 4 spin-orbit multiplet after the action of the CF, because the CF effect for 5f-orbitals is significant. However, there are now a growing number of formally low-symmetry uranium(IV) complexes where with innocent ligands the low-temperature (<2 K) magnetic moments are quite high (R1 m B ), [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] suggesting that something is differentiating these complexes. Empirically, singlet ground states tend to be observed with monoanionic ligands, regardless of the (pseudo)symmetry, and higher magnetic moments have increasingly been observed at low temperatures when stronger di-or trianionic ligands are present, implying a (pseudo)doublet (E) spin-orbit ground state.…”
Section: Introductionmentioning
confidence: 99%